HISTORICAL LEGENDS ON THE ORIGIN AND SETTLEMENT OF THE TRIBALS OF RANCHI DISTRICT, JHARKHAND - Suman Tudu, R K Archana Sada; Sarma, Rabindranath (International Journal of Psychosocial Rehabilitation, 2019)
Legend is a form of modern folklore in which stories told are thought to be true but are likely untrue or distortions and exaggerations of the truth. It is a popular form of modern folklore in today’s society. They are generally fascinating rumors and corporate misdeeds with harrowing details that exhilarate and sometimes instigate their audience. While often containing just a fragment of truth or perhaps none at all, they are generally accepted as factual and enjoy rapid circulation. They are often rooted in local history and popular culture. Legends are a way for us to make sense of the world and manage threats in a safe. In the case of legends, history suggests they will find ways to develop and succeed. The legends are often enhanced and altered to fit a particular region or situation. Folklore, myths, and legends play a predominant role in the lives and life courses of tribes all over the world. The Oraon and the Munda are the major tribes inhabiting the Ranchi district. There are various legends related to these tribes. This paper will discuss the stories outspread about the origin, migration, and settlement of the tribal of Ranchi district. The paper draws its inference from both primary and secondary data. The primary data has been collected from an ethnographic field study in the Ranchi district of Jharkhand. The secondary data has been gathered from published and unpublished sources.